MODEL KURIKULUM ADAPTIF BERBASIS KOMPETENSI ABAD KE-21 DAN LITERASI DIGITAL - Achmad Zailani; Agus Pahrudin; Sri Rahmi (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
ABSTRACT Changes in learning needs, advances in digital technology, and the diversity of educational contexts require a curriculum that goes beyond mere administrative adjustments. This article proposes a conceptual model of adaptive curriculum development that places 21st-century competencies and digital literacy as the primary directions in designing learning experiences. The study employs an integrative literature review of 24 core articles published between 2021 and 2026, complemented by several foundational references to strengthen the conceptual framework. The review process involved keyword identification, source selection based on relevance and academic credibility, full-text reading, thematic coding, and conceptual synthesis. The synthesis integrates five interrelated dimensions: contextual analysis, competency profiles, learning organization, digital literacy, and the implementation ecosystem. Contextual analysis guides the determination of competencies, while learning organization translates these competencies through essential content, active pedagogy, differentiation, and authentic-formative assessment. Digital literacy reinforces the critical, ethical, and responsible use of technology, whereas the implementation ecosystem encompasses teacher professional agency, school leadership, infrastructure readiness, and continuous evaluation. This model positions the curriculum as a dynamic system that assists schools, madrasahs, teachers, curriculum developers, and policymakers in designing contextual, inclusive, and future-responsive learning experiences. ABSTRAK Perubahan kebutuhan belajar, kemajuan teknologi digital, dan keragaman kondisi satuan pendidikan menuntut kurikulum yang mampu bergerak melampaui penyesuaian administratif. Artikel ini merumuskan model konseptual pengembangan kurikulum adaptif yang menempatkan kompetensi abad ke-21 dan literasi digital sebagai arah utama dalam perancangan pengalaman belajar. Kajian dilakukan melalui studi literatur integratif terhadap 24 artikel inti yang diterbitkan pada periode 2021–2026, disertai sejumlah rujukan fundamental untuk memperkuat bangunan konseptual. Penelusuran dilakukan melalui identifikasi kata kunci, seleksi sumber berdasarkan relevansi dan keterverifikasian akademik, pembacaan penuh, pengodean tematik, serta sintesis konseptual. Sintesis tersebut merangkai lima dimensi yang saling berhubungan, meliputi analisis konteks, profil kompetensi, organisasi pembelajaran, literasi digital, dan ekosistem implementasi. Analisis konteks memberi arah bagi penetapan kompetensi, sedangkan organisasi pembelajaran menerjemahkan kompetensi melalui konten esensial, pedagogi aktif, diferensiasi, dan asesmen autentik-formatif. Literasi digital memperkuat penggunaan teknologi secara kritis, etis, dan bertanggung jawab, sementara ekosistem implementasi mencakup agensi profesional guru, kepemimpinan sekolah, kesiapan infrastruktur, serta evaluasi berkelanjutan. Model ini memosisikan kurikulum sebagai sistem dinamis yang membantu sekolah, madrasah, guru, pengembang kurikulum, dan pengambil kebijakan merancang pembelajaran kontekstual, inklusif, serta responsif terhadap perubahan masa depan.